Levantamento do perfil de supervisores clínicos de terapia cognitivo-comportamental no Brasil - BARLETTA, Janaína Bianca; ARAÚJO, Robson Medeiros de; NEUFELD, Carmem Beatriz (Estudos de Psicologia (Campinas), 2023)
Objective This research aimed to identify the profile of Cognitive Behavioral Therapy supervisors in this country and to know their training to exercise this professional activity. Method A nationwide online survey was conducted with 180 Cognitive Behavioral Therapy supervisors, 73.8% of whom were female, with a mean age of 40.3 years (SD = 10.03). Results Among the main results, the intense academic training, training for psychotherapeutic practice and time of clinical experience (12.6 years, SD = 7.64) and supervised experience (7.4 years, SD = 7.26) stand out. Only 27.8% of the participants indicated having received specific training for supervisors and there was a lack of indications of training resources for remote supervision. Conclusion This is considered the first research to outline the profile of Cognitive Behavioral Therapy supervisors in Brazil, expanding the vision on this professional activity.